2005
DOI: 10.1554/04-312
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Burden and Constitution of Major Histocompatibility Complex in the Malagasy Mouse Lemur, Microcebus Murinus

Abstract: We investigated the importance of the major histocompatibility complex (MHC) constitution on the parasite burden of free-ranging mouse lemurs (Microcebus murinus) in four littoral forest fragments in southeastern Madagascar. Fourteen different MHC class II DRB-exon 2 alleles were found in 228 individuals with high levels of sequence divergence between alleles. More nonsynonymous than synonymous substitutions in the functional important antigen recognition and binding sites indicated selection processes maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 61 publications
5
46
1
Order By: Relevance
“…As the parasite antigenicity changes, the relative fitness of the common host genotypes decreases and provides a selective advantage to new, rare MHC alleles to which the parasites are not yet adapted. This hypothesis is supported by both mathematical models (Takahata and Nei, 1990;Borghans et al, 2004) and several studies that showed associations between specific MHC alleles and pathogen resistance (Langefors et al, 2001;Lohm et al, 2002;Froeschke and Sommer, 2005;Harf and Sommer, 2005;Meyer-Lucht and Sommer, 2005;Schad et al, 2005).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…As the parasite antigenicity changes, the relative fitness of the common host genotypes decreases and provides a selective advantage to new, rare MHC alleles to which the parasites are not yet adapted. This hypothesis is supported by both mathematical models (Takahata and Nei, 1990;Borghans et al, 2004) and several studies that showed associations between specific MHC alleles and pathogen resistance (Langefors et al, 2001;Lohm et al, 2002;Froeschke and Sommer, 2005;Harf and Sommer, 2005;Meyer-Lucht and Sommer, 2005;Schad et al, 2005).…”
Section: Introductionmentioning
confidence: 61%
“…Interestingly, also in a closely related mouse lemur species (Microcebus murinus), which lives sympatrically with C. medius in western Madagascar, the DRB locus was duplicated (Schwensow and Sommer, unpublished data). However, no evidence for a MHC-DRB gene duplication was observed in a distant southern Microcebus murinus population (Schad et al, 2005). The fact that duplication events are present in some but not all populations of a species might support the idea that under certain local conditions duplication and coexpression might be advantageous and that locally different selection pressure might affect the evolution of MHC polymorphism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Paterson et al (1998) showed that specific MHC alleles affected both resistance and susceptibility to gastrointestinal nematodes in a natural population of Soay sheep (Ovis aries), as did Meyer-Lucht and in yellow-necked mouse (Apodemus flavicollis) and Schad et al (2005) in Malagasy mouse lemurs (Microcebus murinus). In striped mice (Rhabdomys pumilio), MHC DRB heterozygosity influenced infection status to parasites, and particular alleles occurred more frequently than expected in both high and low parasitised individuals (Froeschke and Sommer, 2005).…”
Section: Parasite-mediated Selection and Mhc Evolutionmentioning
confidence: 98%
“…We amplified exon 2 of the MHC class II gene Drb (Drbexon2) using the 454 GS FLX (Roche) platform. We used the primers JS1 (forward; 59-GAGTGTCATTTCTACAA-CGGGACG-39) and JS2 (reverse; 59-GATCCCGTAGTTG-TGTYTGCA-39) (Schad et al, 2005). The combination of tags in the reverse and forward primers formed unique barcode identifiers and allowed the reassignation of each of the thousands of sequences obtained from the 454 pyrosequencing runs to a unique individual.…”
mentioning
confidence: 99%